KINERJA PERAWAT DALAM MELAKSANAKAN PERAWATAN PADA PASIEN KARDIOVASKULER DI CARDIO VASKULER AND BRAIN CENTER (CVBC) RSUP. Prof. Dr. R. D. KANDOU MANADO - Joice M. Loah; Lendy Magari (POLTEKKES KEMENKES MANADO, 2015)
Performance of nursing or nursing practice is an activity that is given to clients through the implementation of nursing care to achieve the goal of health services in accordance with the duties and responsibilities of nurses to meet the provisions of the code of ethics, professional standards, the right use of health, service standards, and standard operating procedures. The research objective is to get an overview of the performance of nurses in carrying out the treatment in cardiovascular patients in the room CVBC Cardiac Center Dr Prof. Dr R.D Kandou Manado. This research type is descriptive. Population is the patient in the room CVBC. Samples were taken 30% of the total population that is 15 respondents. This study uses monovariabel.The results showed that the image of the nurse's performance in carrying out the treatment in cardiovascular patients there were 8 respondents (53.33%) are performing well, by education level and length of 5 respondents worked 3 respondents. While performing less sebyak 7 respondents (46.67%), based on respondents' education level 4 and 3 respondents working length.Conclusions from the study is the performance of nurses in treating patients in the room CVBC Cardiovascular Hospital. Prof. Dr.DRKandou Manado is said to have not reached the goals and objectives that have been set